A case report of emphysematous gastritis in a diabetic patient: favorable outcome with conservative measures - Asad Jehangir; Andrew Rettew; Bilal Shaikh; Kyle Bennett; Anam Qureshi; Qasim Jehangir (Greater Baltimore Medical Center, 2015)
Emphysematous gastritis (EG) is a rare cause of abdominal pain, which should be differentiated from gastric emphysema. It is hypothesized to result from air-producing microorganisms in patients with underlying predisposing factors. Because of the non-specific presentation of EG, it is diagnosed radiographically. CT scan is the diagnostic modality of choice that typically reveals irregular, mottled appearance of the air in the thickened gastric wall and in the portal vein in the liver. We report a rare case of EG in a male with a history of diabetes mellitus who presented to the emergency department with diarrhea, nausea, vomiting, and epigastric pain. On examination, he was hypotensive and had mild tenderness in the epigastrium. Laboratory tests revealed leukocytosis, elevated lactate, anion gap metabolic acidosis, and acute kidney injury. A non-contrast CT abdomen revealed findings consistent with EG. Even though mortality rate in access of 60% have been reported without prompt surgical intervention in EG, recent literature suggests favorable prognosis with conservative measures in patients without an overt surgical indication. Our patient was also managed conservatively with IV antibiotics and gradual advancement of diet and had complete resolution of symptoms over the ensuing few days. The factors that correlate with a poor prognosis include elevated serum lactate, serum creatinine, and concomitant pneumatosis in small bowel and colon.